The Role of Local Wisdom in Environmental Management for the Realization of Community Rights in the Kajang Community (Literature Study) - Habiba, Habiba; Wulandari, Andi Sri Rezky (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Basically, legislation is needed to organize and restore order to our environment in order to prevent further environmental damage. The Law on Environmental Protection and Management Number 32 of 2009 (UUPLH) was born. However, the fact is that the environmental management law has not fully functioned because environmental damage in Indonesia is still so severe. For this reason, elements and values of local wisdom are needed, especially in the forestry sector. Purpose. The purpose of this study is to determine and analyze the role of local wisdom of the Kajang indigenous people in environmental management in the forestry sector in realizing community rights. Method. The research is normative with library research with statute approach and history approach. Results. The research results and conclusions are the role of local wisdom of the Kajang indigenous people in environmental management in the forestry sector in realizing community rights is a very important role in maintaining the environment and culture and customs of the Kajang indigenous people characterized by (1) The Kajang indigenous people consider the forest a pride that needs to be protected and preserved. Conclusion. This makes the Kajang customary area one of the most preserved areas; (2) interestingly, the Kajang indigenous people are very environmentally conscious.